PEMBERDAYAAN MASYARAKAT MELALUI PENGENALAN MARKETING BERBASIS DIGITAL PADA PELAKU UMKM DI KECAMATAN CIMAHI UTARA KOTA CIMAHI - I Gede Adiputra; Ban Hin; Christopher Sitiunjak (PROSIDING SERINA, 2021)
Changes in marketing behavior from conventional to digital are not balanced by the presence of MSME actors who use digital marketing, even though MSMEs are believed to be able to spur the Indonesian economy. The use of digital technology-based marketing concepts is a hope for MSMEs to develop into economic powerhouses. Digital marketing promotion media is expected to be an effective choice for MSME players in developing business and reaching national and international markets. Conventional promotional media that cost a lot and are much more complicated by themselves are no longer a problem. The purpose of this study is to help MSME business actors use social media as a means for them to promote and provide an understanding of the importance of digital marketing in broadly introducing their products in running a business, family living standards based on individual abilities, availability of resources and potential available. is around, so that later it is hoped that it can be imitated and applied by the village community. Digital marketing training containing the introduction of digital marketing, social media marketing and e-commerce, content marketing and digital marketing management is a means of education and adding insight related to digital marketing for MSME partners. Training on implementing digital marketing strategies for MSME partners has been delivered through workshops and practices during the activity.